EFEKTIVITAS PEMBELAJARAN DARING BERBASIS EDMODO TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA - Muhammad Syahril Harahap; Rahmatika Elindra; Anggi Anggraini Nasution (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to describe the effectiveness of the application of Edmodo-based online learning on the Ability to Understand Mathematical Concepts (AUMC) of students in class VII-1 of SMP Negeri 4 Padangsidimpuan. This research uses descriptive quantitative method with a sample of 15 students.Data collection techniques in this study using observation and tests. Based on the results of the descriptive analysis, it was found: (a) The average application of Edmodo-based online learning was 3.2 with the